Grammatical deficits of Serbian speakers with Broca’s aphasia: A preliminary investigation - Vuković, Mile; Kovač, Ana; Sukur, Željana (Specijalna edukacija i rehabilitacija, 2021)
Introduction. Studies of language deficits in patients with Broca’s aphasia have highlighted agrammatism as a major feature. As the nature of this language deficit is still unknown, further data collection according to the specifics of the particular language is of great importance. Objective. In this paper, we wanted to determine grammatical deficits in Serbian speakers with aphasia. Methods. Using Boston Diagnostic Aphasia Examination, we determined Broca’s aphasia on a sample of 20 subjects, aged 47-70. Speech samples were obtained through two tasks: conversation and picture description. The analysis of samples involved determining the type and subtype of all words and their forms; determining the total number and types of clauses, as well as their functions in a given discourse. Also, the argument structure of the verb was identified. The primary and secondary sentence constituents were determined. Results. The results showed that nouns and full verbs dominate in the speech of patients with Broca’s aphasia. Nouns are most often used in the nominative case, and verbs in the present tense. The ability to use verbs is related to the complexity of their argument structure. Speech is dominated by short utterances whose full meaning is often difficult to determine. Conclusion. Our data show that almost all patients with Broca’s aphasia exhibit grammatical deficits. The general signs of agrammatism are similar to the signs described in other languages. We single out the difficulties in the use of clitics as a prominent characteristic of agrammatism in our respondents.
Keywords: Broca's aphasia; agrammatism; Serbian language